EFEKTIVITAS MODEL PROJECT BASED LEARNING TERHADAP KEMANDIRIAN DAN DISIPLIN BELAJAR SISWA SEKOLAH DASAR - Kasiyanti; Kulsum Nur Hayati (STKIP Subang, 2022)
This study aims to: (1) determine the differences in student learning independence between the experimental class and the control class; (2) knowing the differences in student learning discipline between the experimental class and the control class, (3) knowing the PjBL model is more effective in increasing independence and learning discipline. This research method is a quasi-experimental design with the PjBL model as the experimental class and the direct learning as the control class. The population in this study were all students of Class V SD in Kapanewon Girimulyo Kulon Progo as many as 294 students, while the samples used were 28 students of Class V SD N 1 Jonggrangan as the experimental class and 28 students in class V SD N 2 Jonggrangan as the control class. Data analysis used the Independent t-test to find differences in the use of the PjBL model with Direct Learning and N-Gain Score to determine the effectiveness of each class in increasing students' independence and learning discipline. Based on the results of the study, it was concluded that: a) There were differences in student learning independence between the experimental class and the control class, with a significance value of 0.007 < 0.05; b) There are differences in student learning discipline between the experimental class and the control class, with a significance value of 0.000 < 0.05; c) Learning with the PjBL model is more effective in increasing students' independence and learning discipline.